Cage culture of magur Clarias batrachus (Linnaeus) with selected non-conventional diets in a floodplain wetland of Assam - Borthakur, Sushanta; Goswami, Umesh C (Indian Journal of Fisheries, 2011)
A study was conducted to assess the efficacy of three test diets containing (i) blood meal (BOM), ii) blood meal mixed with papaya peels (BMP) and iii) blood meal mixed with pineapple tops and skin (BMA) in cage culture of Clarias batrachus, keeping fish meal based diet (ROF) as reference diet. The blood meal incorporated either with papaya peels or with pineapple tops and skins as exogenous enzyme sources resulted in better net weight gain, specific growth rate, food conversion and protein efficiency. Fish fed on blood meal alone (BOM) showed inferior growth when compared to the reference diet (ROF). The study suggests the usefulness of replacement of fish meal with exogenous enzymes incorporated into blood meal in the diet of C. batrachus and also indicates that the species can be successfully reared in cages installed in wetlands of Assam.